Heart rate during sleep: Implications for monitoring training status - Waldeck, M. R.; Lambert, M. I. (Journal of Sports Science & Medicine, 2003)
Resting heart rate has sometimes been used as a marker of training status. It is reasonable to assume that the relationship between heart rate and training status should be more evident during sleep when extraneous factors that may influence heart rate are reduced. Therefore the aim of the study was to assess the repeatability of monitoring heart rate during sleep when training status remained unchanged, to determine if this measurement had sufficient precision to be used as a marker of training status. The heart rate of ten female subjects was monitored for 24 hours on three occasions over three weeks whilst training status remained unchanged. Average, minimum and maximum heart rate during sleep was calculated. The average heart rate of the group during sleep was similar on each of the three tests (65 ± 9, 63 ± 6 and 67 ± 7 beats·min-1 respectively). The range in minimum heart rate variation during sleep for all subjects over the three testing sessions was from 0 to 10 beats·min-1 (mean = 5 ± 3 beats·min-1) and for maximum heart rate variation was 2 to 31 beats·min-1 (mean = 13 ± 9 beats·min-1). In summary it was found that on an individual basis the minimum heart rate during sleep varied by about 8 beats·min-1. This amount of intrinsic day-to-day variation needs to be considered when changes in heart rate that may occur with changes in training status are interpreted.